PENINGKATAN HASIL BELAJAR MATEMATIKA DENGAN PENDEKATAN PROBLEM SOLVING SISWA SEKOLAH DASAR - Rusdial Marta (Mathematics Education Study Program, 2017)
This study aimed to describe the application of the model of problem solving to improve learning outcomes flat wake and get up space on the fifth grade students of SDN 018 Langgini. Formulation of the problem in this research is how the application of the model of problem solving to improve mathematics learning outcomes in the wake flat material and geometry in grade students of SDN 018 Langgini. The research was conducted in class V SDN 018 Langgini. This study conducted by two cycles and each cycle held two meetings. The subjects were students of class V SDN 001 Salo totaling 15 people, with the number of male students 5 people, 10 men and women students. Data collection techniques used in this study is the observation, documentation, and testing. Based on the results of this study concluded that in the first cycle is still relatively quite with an average of 74.66, then of 15 students only 9 people or 60% of students who achieve mastery individually. The results of students in the second cycle is in excellent condition with an average of 88.00, and 14 students completed or 93.3% who achieve mastery individually. It can be concluded that with the application of problem solving can improve learning outcomes flat wake and get up space on the fifth grade students of SDN 001 Salo